The effect of firm size on the profitability of the wood- based firms listed in Bursa Malaysia - Govindasamy, Sivadass (2019)
This study is carried out in order to explore the effect of the firm size on the profitability of the wood-based industries listed in Bursa Malaysia. The raw data was obtained from the annual report of a total of 35 wood-based companies between the years 2013 to 2017. The indicator of the firm’s size are the Total Assets and Total Sales while the indicators of the firm’s profitability are Return on Assets (ROA) and Return on Capital Employed (ROCE). The Pearson’s correlation and multiple linear regression have been used in the process of the data analyzing. In this study, the ROCE (dependent variable) shows a significant relationship with Total Asset (independent variable) and Total Sales (independent variable). However, the Total Sales had a greater impact on the ROCE compared to the Total Asset. This study would be a good reference or guide for the business analyst, firm managers or owners of the wood-based companies listed in the Bursa Malaysia in the future.